Relationship between the level of willingness to learn about anti-doping and objective knowledge among Japanese university athletes: A cross-sectional study - Murofushi, Yuka; Kawata, Yujiro; Yamaguchi, Shinji; Nakamura, Miyuki; Takazawa, Yuji; Naito, Hisashi (Frontiers in Sports and Active Living, 2022)
Previous studies have indicated that athletes’ anti-doping knowledge is inadequate. Athletes’ willingness to learn about anti-doping (willingness to learn) may influence their anti-doping knowledge, but the actual situation is unclear. This study aimed to determine the relationship between athletes’ willingness to learn about anti-doping and their objective measurement knowledge and explore directions for educational interventions. The eligible participants were 971 male and 802 female university athletes. We used the ALPHA test (12 questions/4 choices; passing index: ≥ 10 points/80% correct answer rate) to assess objective anti-doping knowledge. The willingness to learn question was “Would you like to learn more about anti-doping?” Responses were given on a 4-point scale ranging from 1: strongly disagree to 4: strongly agree. An ANCOVA was conducted with four levels of willingness to learn as the independent variable and ALPHA correct answer rate as the dependent variable, adjusting for confounding factors (years of athletic experience and anti-doping education experience). The percentage of athletes (%) and each ALPHA correct answer rate (%) by the level of willingness to learn was 1: strongly disagree, n = 1.64%, 61.78%; 2: somewhat disagree, n = 13.1%, 62.38%; 3: somewhat agree, n = 62.9%, 64.08%; 4: strongly agree, n = 22.28%, 67.11%. The ALPHA correct answer rates showed significant differences in the main effect by the level of willingness to learn (F [3, 1767] = 2.873, p < .05, η2 = 0.005), although effect size was low and multiple comparisons showed no significant differences between the levels. The results indicated that the ALPHA correct answer rate did not reach 80% even for the “strongly agree” level of willingness to learn, suggesting that information on anti-doping may be inadequate. The need to provide sufficient educational content to improve knowledge was evident.